Music Therapy for Psychological Well-Being of Chinese University Students: A Systematic Review - Xu Yiwei (Al-Qanṭara, 2025)
Music has the potential to reduce psychological depression and stress, as well as enhance overall well-being in individuals. This phenomenon has been particularly noted among university students, with a focus on China, where depression rates are notably high. Consequently, non-pharmacological interventions have gained attraction among researchers as promising methods to address mental health concerns in university settings. This systematic review aims to investigate the effects of music therapy interventions on mental health and psychological well-being outcomes, specifically among Chinese university students. To achieve this, a thorough search across six databases was conducted to identify relevant studies. Following a meticulous synthesis process, nine published articles were deemed eligible for inclusion, all of which centered on the relationship between music therapy and the mental health of university students. The review findings suggest that music therapy positively impacts the mental health of university students, with indications that it possesses soothing and relaxing qualities. Moving forward, it is recommended that future studies focus on providing detailed descriptions of music therapy interventions and tailor music selections better to suit the psychological health needs of university students.